The Intention Of Using Mobile Banking During Pandemic - Rahmatika Mahmudah; Rosana Eri Puspita (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
The purpose of this study was to determine the effect of perceived usefulness, ease of use, trustworthiness, service quality, and word of mouth on the interest in using mobile banking as a case study of BRI Syariah KC Semarang customers. Data collection was obtained through primary data by distributing questionnaires. The number of respondents used is 60 customers. The data obtained from the respondents is then processed using statistical applications, namely SPSS 23. The data analysis method includes the research instrument test, classical assumption test, determination coefficient test (R2), F test, and T-test. The results show that the perceived usefulness partially has a positive and significant effect on the interest in using mobile banking. Ease of use partially has a positive and insignificant effect on the interest in using mobile banking. Trust partially has a negative and significant effect on the interest in using mobile banking. Service quality partially has a positive and significant effect on the interest in using mobile banking. Word Of Mouth partially has a negative and insignificant effect on interest in using mobile banking. Recommendations for the bank, namely that the bank can renew mobile banking services' facilities so that customers can easily accept the mobile banking service's usefulness and convenience. The bank must also improve security and service quality to maintain customer confidence in mobile banking. Increasing customer networks in mobile banking by doing word of mouth must also be maintained with good messages to reach the public as a recommendation to use mobile banking. The difference between this study and previous research is that this research was conducted during the Covid-19 pandemic. It is expected that the community's behaviour can increase interest in using mobile banking.